Puerto Rico and its Forests - Reddy, C. V. K. (Indian Forester, 1956)
Under Point Four Programme, a brief training course in Tropical Forestry in Riepiedras, Puerto Rico was organized by the U.S. Department of Agriculture and among others from several countries five Forest Officers from India were deputed by the Government of India. The author was one of the candidates so deputed and the present article is based on the knowledge he gained during the tours and lectures conducted in Puerto Rico.